Comparative analysis of the impact of moral sensitivity on service behavior between Chinese and Pakistani nurses - Na Zhang; Xiang Sun; Zhen Xu; Faheem Gul Gilal (BMC Nursing)
Abstract Background The service behavior of nurses is highly important for enhancing the level of hospital nursing care. However, there is currently a lack of research exploring the impact of moral sensitivity on the service behavior of nurses from an ethical perspective. Additionally, less is known about the effects of nationality differences on this relationship. Aim To investigate the relationship between nurses’ moral sensitivity and service behaviors and compare the differences between Chinese nurses and Pakistani nurses. Methods A cross-sectional study was conducted. A total of 742 nurses from China and Pakistan were investigated via the moral sensitivity scale and the service behavior scale from March to May 2023. SPSS and Mplus statistical software were used in the data analysis. Results The moral sensitivity of Chinese nurses significantly positively affects their in-role service behavior (β = 0.311, 95% CI= [0.224, 0.399], p < 0.001) and extra-role service behavior (b = 0.418, 95% CI= [0.334, 0.501], p < 0.001). The moral sensitivity of Pakistani nurses has a significant positive effect on their in-role service behavior (b = 0.178, 95% CI= [0.054,0.303], p < 0.01) and extra-role service behavior (b = 0.135, 95% CI= [0.023, 0.247], p < 0.05). Nationality differences have a significant moderating effect on the relationship between nurses’ moral sensitivity and service behavior (b = 0.298, 95% CI= [0.138,0.438]; p < 0.001; b = 0.520, 95% CI= [0.357,0.682]; p < 0.001). Conclusion Our results indicate that, in both China and Pakistan, nurses’ moral sensitivity positively influences their service behaviors. Furthermore, the moral sensitivity of Chinese nurses has a more significant impact on both in-role and extra-role service behaviors compared to that of Pakistani nurses. These findings may assist healthcare administrators and policymakers in considering national differences when seeking to enhance nurses’ moral sensitivity and, subsequently, improve service behaviors.